Tiktok: Media Baru dan Jalan Terang Dakwah Modern - M Wahyu Abdi Nugroho; Agoes Moh Moefad (Hikmah, 2023)
This study aims to discuss Tiktok as a new media that is now developing and is in great demand by social media users. Islamic da'wah which also definitely needs the media in its activities cannot be separated from the problems surrounding the use of Tiktok as a medium. This study uses a qualitative approach through literature analysis methods related to the research topic. Literature analysis is carried out by collecting various libraries from books or books, journals and other relevant sources. The results of this study indicate that Islam in the perspective of fiqh does not curb the use of Tiktok as a propaganda medium, but Islam regulates with religious boundaries and references regarding what content is allowed in Islam for its use as a propaganda medium.